Peningkatan Hasil Belajar Melalui Problem Based Learning pada Materi Peran Sekolah Bagi Perkembanganku Kelas VII SMP Negeri 6 Menukung Kabupaten Melawi - Markus Setyo Nugroho (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve student learning outcomes on the topic of "The Role of School in My Development" through the implementation of the Problem Based Learning (PBL) model in Grade VII of SMP Negeri 6 Menukung, Kabupaten Melawi. The background of this research is the low student achievement in this subject, indicating a need for a more interactive and contextual teaching approach. The PBL model was chosen because it encourages students to actively engage in critical thinking and problem-solving based on situations relevant to their lives. This study employed Classroom Action Research (CAR) methods, consisting of four stages: planning, action, observation, and reflection, conducted over two cycles. The results showed a significant improvement in student learning outcomes after the implementation of PBL. These findings suggest that PBL is effective in enhancing students' understanding and engagement with the subject matter.